Implikasi CEFR Pada Buku Ajar Sahabatku Indonesia Untuk Penutur Bahasa Arab Level 1 - Ahmad Juliar Fahri; Rinaldi Supriadi (Madah: Jurnal Bahasa dan Sastra, 2023)
To support the needs of the BIPA learning process, textbooks are needed in accordance with the BIPA graduation competency standards (SKL). SKL development refers to the Common European Framework of Reference for Languages (CEFR), a foreign language proficiency guide with three stages, namely A for basic users, B for independent users, and C for proficient users. As a reference for SKL, it is important for BIPA teaching material developers to know the CEFR concept. Because CEFR has a more complex standard of competence. The design of this research is content analysis, focusing on the implications of CEFR Level A1 Sahabatku Indonesia textbook for Arabic Language Speakers Level 1. The results show that CEFR has been implemented in textbooks by presenting four language skills, reading, listening, writing, and speaking, and has supported material aspects of grammar and culture. Textbooks have also been equipped with attractive and interactive digital learning access.